algebra

posted by .

-12x^6+24x^5-18x^2/-6x^2
3x^4+x^3-3x

check see if I did it right.

  • algebra -

    If you meant to type
    (-12x^6+24x^5-18x^2)/(-6x^2) , then

    = 2x^4 - 4x^3 + 3

    If the question is the way you typed it, that is, only the last term is divided by -6x^2 you would get

    -12x^6 + 24x^5 + 3

    there is no logical way of interpretation of your question to get your answer.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. BobPursley..here it is:

    Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common denominator is: (3x+4)(x+1) (x-2)(x+1)/(3x+4)(x+1) - 6x(3x+4)/(x+1)(3x+4) [(x-2)(x+1) - 6x(3x+4)] / (x+1)(3x+4) (x^2 - x - 2 - 18x^2 - 24x) / (x+1)(3x+4) x^2 - 18x^2 = -17x^2 -x …
  2. Algebra

    checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) = 6x*3x = 18x^2 6x*-4 = -24x -1*3x = -3x -1* -4 = 4 18x^2 – 24x -3x +4 = 18x^2 – 27x + 4
  3. Math

    Hello, Having trouble with this one... Solve the inequality: (2x-3)(4x)+x^2=>(3x+4)^2 I did 2x-3*4x 9x^2-12x on the left side on the right side: 9x^2+24x+16 I substracted everything on the right side over to the left and made it …
  4. math

    -12x^6+24x^5-18x^2/-6x^2= -4x^8+4x^7-3x tell me if this right
  5. algebra

    24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
  6. algebra

    -12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for me please
  7. algebra

    Reduce answers to lowest terms. 1.) 2x/2x^2+5x-3 + 5/x^2-9 = 2.) x-3/12x^3-18x^2 - x+1/16x^2-24x = 3.) 2x/x^2-2x-15 - x-2/3x^2+9x =
  8. alg2 check?

    solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x=42 x=42/48 or 7/8 what where the two mistakes made in the problem?
  9. Math

    (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21 <-- my answer but the correct answer is 24x^3-50x^2-23x+21 please correct me?
  10. 9th grade algebra (factoring with quadratic)

    Can you check the following problems? 4. x^2 - 10x +25 = 9 x^2 - 10x + (25 -9) = 9 - 9 x^2 - 10x + 16 = 0 (x - 8)(x-2) = 0 x - 8 = 0, x - 2 = 0 x = 8, x = 2 5. x^2 - 6x + 9 = 49 x^2 - 6x + ( 9 - 49) = 49 - 49 x^2 - 6x - 40 = 0 (x -10)(x

More Similar Questions